2005
DOI: 10.1007/s10295-005-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic production improvement in the rare actinomycete Planobispora rosea by selection of mutants resistant to the Aminoglycosides Streptomycin and Gentamycin and to Rifamycin

Abstract: During a strain improvement program, spontaneous mutants with single or combined resistance to streptomycin (Str(r)), gentamycin (Gen(r)) or rifamycin (Rif(r)) were selected from the industrial strain of Planobispora rosea, which is the producer of thiazolylpeptide GE2270. Among the mutants resistant to each single antibiotic, higher producers occurred more frequently (60%) among Gen(r) than in Rif(r) (10%) and Str(r) (24%) populations. Two Gen(r) mutants showed up to 1.5-fold improvement in GE2270 production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…orientalis Norvancomycinstr rifDouble mutationWang et al (2006) P . rosea GE2270str gen rifTriple mutation in an industrial strainBeltrametti et al (2006) Nonomuraea sp.Glycopeptide A40926 rpoB (H426N, S431N, F445M, S474Y, M581D)"Natural" mutant-type rpoB Vigliotta et al (2005) Streptomyces sp.AntibioticsstrStreptomycin resistanceHai et al (2011)ActinomyceteAntitumor activitystrStreptomycin resistanceHan et al (2009)ActinomyceteAntitumor activitystrStreptomycin resistanceSun et al (2010)ActinomyceteAntitumor activitystrStreptomycin resistanceHan et al (2010)Eubacteria E . coli Cell-free protein synthesis rpsL (K87E)Streptomycin resistanceHosaka et al (2004) E .…”
Section: Impact On Strain Improvementmentioning
confidence: 99%
“…orientalis Norvancomycinstr rifDouble mutationWang et al (2006) P . rosea GE2270str gen rifTriple mutation in an industrial strainBeltrametti et al (2006) Nonomuraea sp.Glycopeptide A40926 rpoB (H426N, S431N, F445M, S474Y, M581D)"Natural" mutant-type rpoB Vigliotta et al (2005) Streptomyces sp.AntibioticsstrStreptomycin resistanceHai et al (2011)ActinomyceteAntitumor activitystrStreptomycin resistanceHan et al (2009)ActinomyceteAntitumor activitystrStreptomycin resistanceSun et al (2010)ActinomyceteAntitumor activitystrStreptomycin resistanceHan et al (2010)Eubacteria E . coli Cell-free protein synthesis rpsL (K87E)Streptomycin resistanceHosaka et al (2004) E .…”
Section: Impact On Strain Improvementmentioning
confidence: 99%
“…are reported in the literature to overproduce secondary metabolites (Beltrametti et al 2006;Hosoya et al 1998;Hu and Ochi 2001;Shima et al 1996). The frequency of higher producers among the resistant Streptomyces spp.…”
Section: Streptomycin-resistant Mutantmentioning
confidence: 94%
“…Beltrametti et al [13] showed that a combination of antibiotic resistance mutations causes elevated production of the thiopeptide GE2270 in the rare actinomycete Planobispora rosea. Individual StrR, RifR, and GenR mutations accounted for 10%, 10%, and 50% increases in GE2270 production, whereas sequential selection of StrR, GenR, and RifR mutations led to an 80% increase in titer, although the actual yields were not disclosed.…”
Section: Combinations Of Antibiotic Resistance Mutationsmentioning
confidence: 99%